Srpski Srpski - Dudaš, Atila (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
According to the Directive 1999/44/EC on certain aspects of the sale of consumer goods and associated guarantees the seller is solely responsible for non-conformity. The majority opinion was that there was no need to establish producer’s direct liability by the legislation of the EU. However, due to its minimalistic legislative approach, the Directive enables Member states to maintain or introduce more stringent rules in order to achieve higher level of consumer protection, including rules on producer’s direct liability for non-conformity. A relatively smaller number of member states used this opportunity to maintain or introduce regulation on producer’s direct (or subsidiary) liability for non-conformity. Producer’s direct liability is not envisaged by the new Directive (ЕU) 2019/771 either.In the Serbian law the Consumer Protection Act from 2010 envisaged producer’s subsidiary liability for non-conformity. The Act from 2014 replaced this with the rule on the seller’s right to claim redress from the producer in the distribution chain for the obligations performed towards the consumers on the grounds of non-conformity. This approach is supported in the new Act from 2021. The lack of the producer’s direct or subsidiary liability puts the consumer in a precarious position in which he or she may not enforce the rights based on non-conformity, if the seller had ceased to exist or had become insolvent, especially taking into account that as of 2005, the producer’s guarantee became voluntary. Such a state of regulation may be considered inappropriate. In this paper a proposal is made to (re)introduce the producer’s compulsory guarantee for technical goods, supplemented by producer’s subsidiary liability for non-conformity. As an argument in favor of the proposal the example of the Hungarian law may be posed, in which the producer’s compulsory guarantee and the producer’s (direct) liability for non-conformity exist in parallel and well-synchronized. Both the producer’s compulsory guarantee and their subsidiary liability for non-conformity should be limited to defects and other causes of non-conformity that fall within the producer’s sphere of control. Similarly to the Hungarian law, the producer’s liability should be limited to repair or replacement of the defective or non-conforming product, which are the consumer’s primary remedies.